Handbook of pest management in organic farming - Vacante, Vincenzo; Kreiter, Serge (CABI, 2018)
An up-to-date, comprehensive reference for pest management in organic systems, including practical advice, tables and diagrams. Introductory chapters explore the management of crops to prevent outbreaks, plant protection tools, natural enemies and pest control. Crop-based chapters discuss geographic distribution, economic importance and key pests